ØªØ·Ø¨ÙŠÙ‚ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„ÙˆÙ…Ø¶ÙŠØ© (Flash Card) ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ù‚Ù…Ø± Ø§Ù„Ù‡Ø¯Ù‰ ÙÙŠÙ†Ø¨ÙˆÙˆÙ† Ù„ÙˆÙ…Ø¨ÙˆÙƒ Ø§Ù„ØºØ±Ø¨ÙŠØ© - Mendur Wahyuni; Suparmanto Suparmanto; L. Ahmad Busyairi (Lughatu Ad-Dhat, 2023)
The purpose of this study is to find out how the application of flash card in mufrodat learning in class VII at MTs Qamarul Huda Pembuwun, to find out the problems in the application of flash card and what are the solutions to the problem. This study uses a descriptive qualitative approach, namely to describe the data obtained in the field. The data collection method used is the interview observation method and the documentation method to obtain school data such as the history of the establishment of MTs Qamarul Huda Pembuwun, the number of teachers and students, and the completeness of school infrasucture. The results of this study indicate that the application of flash card in mufrodat learning so that students are able to memorize the mufrodat and remember the mufrodat that have been memorized easily without feeling bored because the application of flash cards is carried out directly by the students themselves and is applied with games so that students become more happy and interested them to learn Arabic is increasing.